2020
DOI: 10.3390/quat3030021
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Disappearance of Microblade Technology in the Terminal Pleistocene of Hokkaido, Northern Japan: Looking at Archaeological and Palaeoenvironmental Evidence

Abstract: Archaeological research, for several decades, has shown that various microblade technologies using obsidian and hard shale appeared and developed from the Last Glacial Maximum to the terminal Pleistocene (Bølling–Allerød–Younger Dryas) in Hokkaido, Northern Japan. It is well accepted that microblade technology was closely related to the high mobility of foragers to adapt to harsh environments. Recent archaeological and palaeoenvironmental evidence from Hokkaido demonstrates that the disappearance of microblade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, let me make two comments that might be useful in understanding why microblade technology disappears. First, Takakura [5] and Zhang [8] associate the decline in microblade technology with the demise of the large Pleistocene fauna of Hokkaido-and that association indeed appears to be true. Although in the US, large fauna, including mammoths and mastodons were hunted with Clovis spearpoints, large bifacial points, a technology that, invented by a population that migrated to North America from Asia about 15,000 years ago, almost certainly came out of a microblade tradition.…”
Section: Technologymentioning
confidence: 97%
See 1 more Smart Citation
“…However, let me make two comments that might be useful in understanding why microblade technology disappears. First, Takakura [5] and Zhang [8] associate the decline in microblade technology with the demise of the large Pleistocene fauna of Hokkaido-and that association indeed appears to be true. Although in the US, large fauna, including mammoths and mastodons were hunted with Clovis spearpoints, large bifacial points, a technology that, invented by a population that migrated to North America from Asia about 15,000 years ago, almost certainly came out of a microblade tradition.…”
Section: Technologymentioning
confidence: 97%
“…Takakura [5] looks at the archaeology of Hokkaido, Japan's northern island. Here he finds, as others have, that microblade technology disappears during the Younger Dryas (YD) cooling, perhaps, quite possibly, because the human population itself disappears at this time (although the ages of the boat-shaped tool assemblages are not well dated and may fall within the YD).…”
Section: The Case In Asiamentioning
confidence: 99%
“…To allow for a comprehensive discussion based on lithic records from various regions, concepts used to classify and describe archaeological materials should be distinguished from those used for behavioural interpretation. Therefore, to investigate the spatiotemporal variation of lithic assemblages across North and Northeast Asia from MIS 3 to MIS 2, the research could, first, define a microblade according to morphometric criteria (microblade refers to parallel-sided small artefacts possessing one or more ridges running parallel to their long axes, generally 4-10 mm wide and 1-2 mm thick) [82] and select the lithic assemblages to be analysed from that definition. From these, the diversity and interrelationship of microblade technology across various regions should be investigated using technological and functional perspectives.…”
Section: No Obvious Ripples On the Lower Face;mentioning
confidence: 99%
“…This may have been the case because the diverse natural resources of forests, rivers and sea in the Japanese archipelago were abundant, secure, and stable. In fact, it has been revealed that human cultures changed from the late Pleistocene to the early Holocene in Hokkaido [18]. In the eastern part of Hokkaido the discovery of many early Holocene pit dwellings are evidence that the number of settlements was increasing, suggestive of higher population densities, or growing sedentism, or both.…”
mentioning
confidence: 99%